Analisis Eksternalitas Positif Program “Wisata Alam 21” Desa Aji Mesir Kecamatan Gedung Aji Kabupaten Tulang Bawang - Eko Ardianto Ardianto; Moneyzar Usman (Goodwood Publishing, 2022)
This study aims to analyze the differences in the economic and social conditions of the community before and after the Wisata Alam 21 program in Aji Mesir Village, Gedung Aji District, Tulang Bawang Regency. The aspects studied in this study are aspects of economic conditions, and social conditions. The research method used in this study is a descriptive-comparative method with a qualitative approach. The data analysis method in this study used a different test analysis with the Wilcoxon Signed Rank Test. The results showed that there was a significant difference between economic conditions, and social conditions, before and after the Wisata Alam 21 program felt by the people of Aji Mesir Village, Gedung Aji District, Tulang Bawang Regency.